PROSEDUR PEMERIKSAAN AKUNTANSI AKUN UTANG PADA KAP BS - Mufidah, Salma Fitria; Budiwitjaksono, Gideon Setyo (Program Studi Akuntansi Universitas Flores, 2026)
The purpose of this study is to improve our understanding of the audit process, particularly the audit process for accounts payable at Public Accounting Firm (KAP) BS. The main focus of this study is how auditors design and implement procedures to ensure that accounts payable balances are correctly recorded and presented in the financial statements. This study uses a qualitative descriptive approach and collects data from KAP BS auditors through interviews, observations, and literature studies. The results indicate that KAP BS auditors have implemented audit procedures for their accounts payable in accordance with auditing standards. To examine accounts payable, auditors perform tests of controls, third-party confirmations, and subsequent events. These account checks are conducted to ensure that the balances in the financial statements are correctly presented.